Socioeconomic factors associated with the illegal purchase of tobacco products in Panama - Víctor H Herrera-Ballesteros; Julio Zúñiga; Ilais Moreno; Beatriz Gómez; Reina Roa-Rodríguez (Instituto Nacional de Salud Pública, 2017)
Objective. To characterize the illegal purchase of to- bacco products in Panama and the assocation with sociodemographic and socioeconomic variables. Materials and methods. Study population derived from the Global Adult Tobacco Survey (GATS) conducted in 2013. The association of sociodemographic and socioeconomic variables with illegal purchase of tobacco products was estimated by means of logistic regression models. Results. Men, age group 15 to 39, no formal education, non-governmental, inactive employees, current smoking, lowest quintile of income and living in rural areas were factors associated with the illegal purchase of tobacco products. Conclusions. Sociodemographic and socioeconomic factors play an important role in the illegal purchase of tobacco products. These results suggest the im- portance of surveillance over illicit trade and of the effective implementation of the current laws.